1998
DOI: 10.1046/j.1365-2842.1998.00315.x
|View full text |Cite
|
Sign up to set email alerts
|

Artificial caries formation around fluoride‐releasing restorations in roots

Abstract: Secondary caries is one of the most important factors leading to replacement of dental restorations. This investigation assessed the capacity of fluoride-releasing restorative materials to resist caries in vitro when used in roots. Class 5 cavities were prepared in the buccal and lingual surfaces of 30 extracted premolars. The six materials used were: glass-ionomer cement (Fuji), glass-ionomer cement with silver particles added (Ketac-silver), fluoride-containing composite resin (Tetric), composite resin (Silu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0
11

Year Published

2000
2000
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 18 publications
0
26
0
11
Order By: Relevance
“…On the other hand, its physicochemical bonding to dentin could have inhibited bacterial percolation through the tooth/restoration interface [Dionysopoulos et al, 1994;ten Cate and van Duinen, 1995;ten Cate et al, 1995;Mertz-Fairhurst et al, 1995;Francci et al, 1999].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, its physicochemical bonding to dentin could have inhibited bacterial percolation through the tooth/restoration interface [Dionysopoulos et al, 1994;ten Cate and van Duinen, 1995;ten Cate et al, 1995;Mertz-Fairhurst et al, 1995;Francci et al, 1999].…”
Section: Discussionmentioning
confidence: 99%
“…10 The high-fluoride release and recharge properties of giomers minimize recurrent caries and demineralization. 11 Based on several studies, [12][13][14][15][16] giomers have a reported caries inhibiting effect of 14%-35% compared to nonfluoride-releasing restorative materials.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] A number of studies have suggested that the fluoride released from glass ionomer cements can reduce the demineralization of the surrounding dentin or enamel and favor the remineralization of lesions close to the restoration wall. [6][7][8][9] Glass ionomer cements contain calcium fluoroaluminosilicate glass, which is attacked by polyacids to release cations and fluoride ions. These ions react with polyanions to form a salt gel matrix that presents small particles of silica gel containing fluoride crystallites.…”
Section: Introductionmentioning
confidence: 99%